PEMANFAATAN BATU APUNG SEBAGAI ADSORBEN DALAM APLIKASI KOLOM ADSORPSI UNTUK PENYISIHAN LOGAM KROMIUM DARI AIR TANAH - Indah, Shinta; Helard, Denny; Herdiani, Febbi (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2024)
The utilization of pumice as an adsorbent has been tested in adsorption column applications in removing chromium (Cr) from groundwater. The pumice was taken from the banks of the Pasak River, Pariaman, West Sumatra. The column used is made of glass with 130 cm in height and 2,6 cm in diameter. The experiment was carried out by varying the bed height (65, 75, and 85 cm) and the influent flow rate (2, 3, and 4 gpm/ft2), while the influent concentration used was according to the groundwater sample conditions. The concentration of Cr was analyzed using inductively coupled plasma emission (ICPE). The performance of the adsorption column can be evaluated from the breakthrough curve, which is a plot between the Ct/C0 ratio and the sampling time. The experimental results showed that the optimum condition with the highest removal efficiency of 65.15% and an adsorption capacity of 0.0031 mg/g were obtained at a bed height of 85 cm and an influent flow rate of 2 gpm/ft2. Based on the experimental results, it was concluded that Cr removal efficiency increased as the influent flow rate decreased and as the bed height of adsorbent increased. The adsorption column with Sungai Pasak Pariaman pumice as an adsorbent has potential to be applied in removing Cr metal from groundwater.